2014
DOI: 10.1371/journal.pone.0100085
|View full text |Cite
|
Sign up to set email alerts
|

Hydrographic Processes Driven by Seasonal Monsoon System Affect Siphonophore Assemblages in Tropical-Subtropical Waters (Western North Pacific Ocean)

Abstract: This work is a part of the Taiwan Cooperative Oceanic Fisheries Investigation, the first large scale hydrographic and plankton survey around Taiwan (21–26°N, 119–123°E). The present study examined the influence of hydrodynamic and biological variables driven by monsoon system on the siphonophore assemblages through an annual cycle in 2004. Calycophorans, namely Chelophyes appendiculata, Diphyes chamissonis, Lensia subtiloides, Bassia bassensis, and Muggiaea atlantica, were the most dominant siphonophore specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…The seasonal distribution and abundance of siphonophores are primarily attributed to fluctuations in environmental factors that control the sexual cycle 33 , 34 , and in a favorable environment, siphonophores can rapidly reproduce asexually 35 37 . In the western North Pacific Ocean, spatiotemporal variation in siphonophore assemblages is closely related to temperature, salinity, chlorophyll concentration, and zooplankton abundance, which are strongly influenced by ocean currents 38 and seasonal monsoons 39 . For instance, in summer, the southwestern monsoon increases the species number and abundance of siphonophores, whereas in winter the northeast monsoon decreases species number and abundance 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal distribution and abundance of siphonophores are primarily attributed to fluctuations in environmental factors that control the sexual cycle 33 , 34 , and in a favorable environment, siphonophores can rapidly reproduce asexually 35 37 . In the western North Pacific Ocean, spatiotemporal variation in siphonophore assemblages is closely related to temperature, salinity, chlorophyll concentration, and zooplankton abundance, which are strongly influenced by ocean currents 38 and seasonal monsoons 39 . For instance, in summer, the southwestern monsoon increases the species number and abundance of siphonophores, whereas in winter the northeast monsoon decreases species number and abundance 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise the species observed here from the CPO have all been recorded previously in the Pacific Ocean (Alvariño, 1971; Pagès et al , 1990). Species such as A. eschscholtzii , Abylopsis tetragona , B. bassensis , C. appendiculata , C. contorta , E. spiralis , M. atlantica , S. chuni and S. quadrivalvis are widely distributed in tropical waters of the Eastern Pacific (Gasca & Suárez, 1992a, b) and the Caribbean (Gasca, 1999), further west in the tropical Pacific (Pagès et al , 1990; Lo et al , 2012, 2014; Hsieh et al , 2013) as well as cooler Chilean (Palma, 1999; Palma & Silva, 2004) and Peruvian (Ayón et al , 2008) waters. Most species of siphonophore have a near global distribution (Mackie et al , 1988), with all of the species found here reported from either the Atlantic (Pugh, 1999) or the Indian oceans (Daniel, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In waters of the Mediterranean Sea, Fernández de Puelles et al (2007) found a positive correlation between the abundance of Muggiaea , Lensia , Eudoxoides and Abylopsis , and abundance of copepods. In subtropical waters of Taiwan, Lo et al (2014) suggested that the abundance and distribution of siphonophores are related to zooplankton biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the increase of upper layer nutrients levels through mixing, terrestrial outflow is the main source of nutrients in the Gaoping waters [33,34]. Plentiful nutrients have entrained higher phytoplankton production, which were the food resources for grazers such as copepods and their predators, such as gelatinous carnivores and fish larvae [61][62][63]. However, climateassociated fluctuations in the timing and amount of precipitation influence river discharge, which in turn affects the entrainment of nutrients and the magnitude of phytoplankton production [21,64].…”
Section: Discussionmentioning
confidence: 99%